Opportunistic feeding strategy in wild immature chimpanzees: Implications for children as active foragers in human evolution. Issue 133 (August 2019) - Matsumoto, Takuya
Abstract: Modern human ( Homo sapiens ) children are generally considered to be dependent on older individuals for foods, even after weaning. However, recent studies of hunter-gatherer societies have reported that children can also acquire food by themselves, although the degree of self-provisioning by children differs among groups and is considered a facultative adaptation. To investigate the dependence of children on older individuals for food and the importance of self-provisioning in early hominins, I examined feeding behavior in wild, immature chimpanzees ( Pan troglodytes schweinfurthii ). I studied 19 mother-offspring chimpanzee pairs in the Mahale Mountains National Park, Tanzania for approximately 22 months. Feeding behavior and interactions between mothers and their offspring were recorded. The results supported these three predictions: (1) immature chimpanzees need to feed more frequently than mothers because of increased basal metabolic rate and immature stomach capacity; (2) mothers provide effective opportunities to feed on high-quality food items which are similar to those of the mothers'; and (3) when feeding independently of their mothers, immature chimpanzees consume highly accessible food including non-adult foods nearby mothers to avoid getting lost and physical burden as with self-provisioning of human children in hunter gatherer societies. During non-simultaneous feeding bouts, immature individuals frequently consumed pith and wood. They may be valuable food items for immature individuals during their growth stage because they can be consumed year round and contain relatively higher crude ash and protein amounts, which may enable immature chimpanzees to manage the confines of their immature bodies, preventing them from matching adult feeding rhythms. This opportunistic feeding strategy is similar to self-provisioning by human children in hunter-gatherer societies. These results suggested that early hominin children performed self-provisioning based on opportunistic feeding strategies, and contributed to their food consumption by snacking in accordance with their metabolic needs and physical confines.